2022
DOI: 10.3390/app12168062
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Analysis of the Distribution Parameters of a Metal Dot Array in a SAW Gyroscope

Abstract: A surface acoustic wave (SAW) gyroscope has many unique advantages, but a low detection sensitivity limits its development. Previous studies have shown that adding a metal dot array to the acoustic wave propagation path of the SAW delay line can enhance the Coriolis force and further improve sensitivity. Therefore, in order to optimize the detection sensitivity performance of the sensor, 128°YX-LiNbO3, ST-X Quartz and X112°Y-LiTaO3 piezoelectric substrates were selected by finite element method to analyze the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
(58 reference statements)
0
0
0
Order By: Relevance
“…Since the reflectivity of SiO 2 is greater than that of STX quartz, it can be concluded that if the reflection coefficient of the lower-layer material is greater than that of the upper-layer material, the energy propagated into the substrate will be more significantly reflected back into the upper layer, causing interference with the Rayleigh wave propagating on the substrate surface and weakening the SAW gyroscopic effect. In our previous research, we found that different substrate structures have different requirements in terms of the optimal size of the metal dot array [26]. Moreover, during the simulation, we observed another phenomenon, whereby the addition of non-piezoelectric materials below the piezoelectric material could also change the optimal size of the metal dot array.…”
Section: The Influence Of the Reflection Coefficient On The Saw Gyros...mentioning
confidence: 70%
See 2 more Smart Citations
“…Since the reflectivity of SiO 2 is greater than that of STX quartz, it can be concluded that if the reflection coefficient of the lower-layer material is greater than that of the upper-layer material, the energy propagated into the substrate will be more significantly reflected back into the upper layer, causing interference with the Rayleigh wave propagating on the substrate surface and weakening the SAW gyroscopic effect. In our previous research, we found that different substrate structures have different requirements in terms of the optimal size of the metal dot array [26]. Moreover, during the simulation, we observed another phenomenon, whereby the addition of non-piezoelectric materials below the piezoelectric material could also change the optimal size of the metal dot array.…”
Section: The Influence Of the Reflection Coefficient On The Saw Gyros...mentioning
confidence: 70%
“…Additionally, the non-piezoelectric layer was set to 2λ, and a Perfectly Matched Layer (PML) with a thickness of 1λ was set at the bottom to absorb SAW and prevent reflection from affecting the simulation results [40]. Although the distribution of metal dot arrays along the acoustic wave propagation path has been shown to effectively enhance the Coriolis force [25,41], in SAW angular velocity sensors, the size of the metal dot array in terms of length, width, and thickness changes the proportions of the elastic wave energy in the metal dot array, as roughly shown in Figure 3, and the optimal size of the metal dot array varies with the material [26]. Previous research has shown that with increased thickness of the metal dot array, the SAW gyroscopic effect becomes stronger [21], but in this study, we chose a metal dot thickness of 0.9 um due to technological limitations.…”
Section: Modelingmentioning
confidence: 99%
See 1 more Smart Citation